2012
DOI: 10.4172/2161-1459.s5-001
|View full text |Cite
|
Sign up to set email alerts
|

International Expansion of the Use of Pharmacotherapies for the Treatment of Opioid Dependence

Abstract: Until recently, the global availability and consumption of opioid agonists and psychotropic medications have been below the levels needed for research to demonstrate local efficacy and to develop local evidence-based best medical practices. In addition, the global availability and use of opioid agonists and psychotropic medications have not been sufficient to implement the well documented efficacy shown for the treatment of opioid dependence that has been developed by research over the last 40 years. This stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, different treatment modalities, especially with methadone, have to be accompanied by behavioral treatment. Research has in fact shown the absence of the latter to increase the frequency of relapse ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, different treatment modalities, especially with methadone, have to be accompanied by behavioral treatment. Research has in fact shown the absence of the latter to increase the frequency of relapse ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methadone is the preferred pharmacotherapy for resource limited setting because of its lower cost compared to other medications. Globally since 2000, there has been a rapid expansion of medication-assisted treatment, mainly using methadone, in the context of HIV prevention, care and treatment programs [88]. The integration of substance abuse treatment and HIV care and treatment is an effective and cost efficient health service platform to provide care and treatment for HCV/HIV co-infection in a resource limiting setting [89].…”
Section: Pharmacologic Treatments For Substance Use Disordersmentioning
confidence: 99%
“…However, a strong research base in Western countries has resulted in the development of evidence-based medical practices using opioid agonists in maintenance treatment regimens and opioid antagonists in relapse prevention strategies. The recognition of these evidence-based medical treatment for opioid abuse and dependence has resulted in a substantial global increase in the medical use of opioid agonists and psychotropic medications to address opioid dependence [2830]. This increase is particularly evident in the initiation of new pharmacotherapy programs in regions of Europe, North America, Africa, Asia, and Oceania.…”
Section: Substance Abuse Treatment As Hiv Prevention and Part Of Tmentioning
confidence: 99%